Preemptive Analgesia, Including Morphine, Does Not Affect Recovery Quality and Times in Either Pain-Free Horses or Horses Undergoing Orchiectomy - Taffarel, Marilda Onghero; Luna, Stelio Pacca Loureiro [UNESP]; Cardoso, Guilherme Schiess; de Oliveira, Flavia Augusta; Alonso, Juliana de Moura [UNESP]; Gozalo-Marcilla, Miguel [UNESP] (Elsevier, 2017)
Recovery quality and times from general anesthesia in horses may be influenced by surgery, analgesia with morphine or combinations of both. Twenty-three adult healthy horses were enrolled in this prospective experimental trial in a clinical setting and were randomly allocated to one of the following groups: anesthesia only (GA; n = 6), preemptive analgesia and anesthesia (GAA; n = 5), anesthesia and castration (GC; n = 6), or preemptive analgesia, anesthesia, castration, and intraoperative local analgesia (GCA; n = 6). All horses were sedated with intramuscular (IM) xylazine (0.5 mg/kg). Anesthesia was induced with intravenous (IV) guaifenesin (100 mg/kg) and thiopental (5 mg/kg) and maintained with isoflurane in oxygen. Animals in groups with preemptive analgesia received IM morphine (0.2 mg/kg) and dipyrone (10 mg/kg) and IV flunixin meglumine (1.0 mg/kg) immediately before sedation. Recoveries from general anesthesia were rope-assisted. Recovery scores (from 8 [excellent recovery] to 70 [worst recovery]) and times were compared between groups, using a one-way analysis of variance followed by a Tukey's test (P <.05). Mean ± standard deviation (SD) and range recovery scores were 22 ± 14 (8–45), 9 ± 2 (8–12), 14 ± 5 (8–22), and 12 ± 1 (10–13) in groups GA, GAA, GC, and GCA, respectively. Mean ± SD times to stand in minutes were 21 ± 10, 18 ± 7, 33 ± 12, and 35 ± 21 in groups GA, GAA, GC and GCA, respectively. No statistically significant differences were found for any of the variables. Neither preoperative administration of analgesics, including morphine, nor castration interfered with the recovery qualities and times in horses undergoing general anesthesia. Preemptive morphine did not worsen anesthetic recovery quality in horses.
Keywords: Anesthesia recovery period; Equine; Opioid; Preemptive analgesia